2017
DOI: 10.1097/bot.0000000000000779
|View full text |Cite
|
Sign up to set email alerts
|

Is Early Definitive Fixation of Bicondylar Tibial Plateau Fractures Safe? An Observational Cohort Study

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 38 publications
1
28
1
Order By: Relevance
“…The results of open reduction and internal fixation in Type V and VI Schatzker tibial plateau fractures are summarised in Table 5 . 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 Though the data is not objectively comparable due to lack of homogeneity between various studies, it can be inferred from Table 4 , Table 5 that internal fixation is associated with more number and frequency of complications.…”
Section: Discussionmentioning
confidence: 99%
“…The results of open reduction and internal fixation in Type V and VI Schatzker tibial plateau fractures are summarised in Table 5 . 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 Though the data is not objectively comparable due to lack of homogeneity between various studies, it can be inferred from Table 4 , Table 5 that internal fixation is associated with more number and frequency of complications.…”
Section: Discussionmentioning
confidence: 99%
“…Common practice favors staged protocol with spanning fixators [13, 31]. A recent retrospective cohort study reporting the results of early definitive fixation (within 72 h of injury) of bicondylar tibial plateau fractures (AO/OTA 41-C) showed a favorable 2.9% incidence rate of ACS [32]. However, this study might have been biased by the fact that the choice of timing and protocol was left at the discretion of the attending surgeon, potentially leading to lower Injury Severity Score (ISS) in the early definitive fixation group (11 vs. 17, p  = 0.024) and to a strong trend for patients with open fractures to sustain a staged protocol (28,6% open fractures in the staged protocol group vs. 5.0% in the early definitive fixation population, p  = 0.012).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported acceptable results in both tibial pilon and plateau fractures in appropriately selected patients using contemporary surgical techniques. 24,25 Unno et al recently reported on a cohort of 102 non-consecutive OTA/AO 41C fractures, most treated in one stage less than 72 hours from injury. 24 They treated 91% with one operation, and 82% of these were treated with ORIF mostly (71%) through a single lateral approach.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…24,25 Unno et al recently reported on a cohort of 102 non-consecutive OTA/AO 41C fractures, most treated in one stage less than 72 hours from injury. 24 They treated 91% with one operation, and 82% of these were treated with ORIF mostly (71%) through a single lateral approach. They had an aggressive interpretation of soft tissue readiness, only using two-stage treatment in the face of circumferential blisters, necrosis, and medical issues preventing early surgery.…”
Section: A C C E P T E Dmentioning
confidence: 99%
See 1 more Smart Citation